An evaluation of the reactivity of synthetic Fe-Ni oxygen carriers: CO oxidation, H2O reforming, and toluene cracking. (15th July 2021) - Lin, Yan; Zhang, Zhen; Wang, Haitao; Fang, Shiwen; Huang, Zhen; Chen, Tianju; Wei, Guoqiang; Zhao, Kun; Zhao, Zengli; Wu, Jinhu; Fang, Yitian; Li, Haibin
Graphical abstract: Highlights: Evaluation of the reactivity of oxygen carriers using DAEM-TI. DAEM-TI under an isothermal situation. The compensation effect of the DAEM-TI. CO oxidation, H2 O reforming, and toluene cracking of NiFe2 O4 . Reactivity tests for NiFe2 O4 with inert supports. Abstract: NiFe2 O4 is an ideal oxygen carrier for the chemical looping process. This study focused on the evaluation of NiFe2 O4 reactivity in relation to CO oxidation, H2 O reforming and toluene (model tar) cracking. The NiFe2 O4 was synthesized by the coprecipitation (CP), solid state (SS) and sol–gel (SG) methods for the TG and fixed bed experiments. We proposed a distributed activation energy model of the time integral, namely, DAEM-TI, for the evaluation of the reactivity of NiFe2 O4 for CO oxidation (nonisothermal condition) and H2 O reforming (isothermal condition). The goodness of the model fitting agreed well with the experimental data for CO oxidation (nonisothermal condition) but was slightly worse for H2 O reforming (isothermal condition). The average activation energy, Emean, obtained by DAEM-TI was successfully used to determine the reactivity rank for different oxygen carriers. Emean analysis showed that the reactivity rank for CO oxidation was determined to be sample SG, sample SS and sample CP, and for H2 O reforming, the rank determined to be sample CP, sample SG and sample SS. These results agreed well with TG analysis, and this finding will inspire the applications of the DAEM. In general, the sample SG showed better reactive performance for CO oxidation, H2 O reforming and toluene cracking compared to the other samples. The inert support significantly increased the multiple redox cycle reactivity of NiFe2 O4, and the improvement due to the inert support was ranked as follows: ZrO2 ≈Al2 O3  > TiO2 (anatase) > TiO2 (rutile) > SiO2 .